Inkjet printed periodical micropatterns made of inert alumina ceramics induce contact guidance and stimulate osteogenic differentiation of mesenchymal stromal cells. (15th October 2016) - Lauria, Ines; Kramer, Michael; Schröder, Teresa; Kant, Sebastian; Hausmann, Anne; Böke, Frederik; Leube, Rudolf; Telle, Rainer; Fischer, Horst
Graphical abstract: Abstract: Bioinert high performance ceramics exhibit detrimental features for implant components with direct bone contact because of their low osseointegrating capability. We hypothesized that periodical microstructures made of inert alumina ceramics can influence the osteogenic differentiation of human mesenchymal stromal cells (hMSC). In this study, we manufactured pillared arrays made of alumina ceramics with periodicities as low as 100 μm and pillar heights of 40 μm employing direct inkjet printing (DIP) technique. The response of hMSC to the microstructured surfaces was monitored by measuring cell morphology, viability and formation of focal adhesion complexes. Osteogenic differentiation of hMSCs was investigated by alkaline phosphatase activity, mineralization assays and expression analysis of respective markers. We demonstrated that MSCs react to the pillars with contact guidance. Subsequently, cells grow onto and form connections between the microstructures, and at the same time are directly attached to the pillars as shown by focal adhesion stainings. Cells build up tissue-like constructs with heights up to the micropillars resulting in increased cell viability and osteogenic differentiating properties. We conclude that periodical micropatterns on the micrometer scale made of inert alumina ceramics can mediate focal adhesion dependent cell adhesion and stimulate osteogenic differentiation of hMSCs.